A review of optimization techniques used in the design of fibre composite structures for civil engineering applications - Awad, Ziad K.; Aravinthan, Thiru; Zhuge, Yan; Gonzalez, Felipe (Materials in engineering, 2012)
► We reviewed existing optimization techniques of fibre composite structures. ► Proposed an improved methodology for design optimization. ► Comparison showed the MRDO is most suitable. Fibre composite structures have become the most attractive candidate for civil engineering applications. Fibre reinforced plastic polymer (FRP) composite materials have been used in the rehabilitation and replacement of the old degrading traditional structures or build new structures. However, the lack of design standards for civil infrastructure limits their structural applications. The majority of the existing applications have been designed based on the research and guidelines provided by the fibre composite manufacturers or based on the designer’s experience. It has been a tendency that the final structure is generally over-designed. This paper provides a review on the available studies related to the design optimization of fibre composite structures used in civil engineering such as; plate, beam, box beam, sandwich panel, bridge girder, and bridge deck. Various optimization methods are presented and compared. In addition, the importance of using the appropriate optimization technique is discussed. An improved methodology, which considering experimental testing, numerical modelling, and design constrains, is proposed in the paper for design optimization of composite structures.